Sociocultural–psychological predictors influencing parents' decision-making regarding HPV vaccination for their adolescent daughters in mainland China: An extended TPB model - Zhang, Lingmin; Yang, Jian; Cao, Ye; Kang, Wanying (Frontiers in Public Health, 2023)
Introduction Enhancing human papillomavirus (HPV) vaccine uptake rates to protect women's health is an important public health issue worldwide. China has taken a series of measures in recent years to promote HPV vaccination among school-aged girls, but the vaccine uptake rate remains low. Investigating the factors influencing vaccination-related decision-making of adolescent girls' parents is key to solving the problem. This study aimed to examine the influence of sociocultural-psychological predictors, including exposure to HPV-related stories (positive/negative), affective reactions (pride/regret), injunctive norms on the Internet and perceived moral obligation, on parents' HPV vaccination-related decision-making for girls aged 13–15 years in mainland China. Methods A cross-sectional online survey using quota sampling was conducted in February 2022. Four hundred and five valid and qualified questionnaires were obtained. Partial least squares structural equation modeling was performed by SmartPLS 3 (i) to evaluate the reliability and validity of the measurement models of 11 constructs, and (ii) to test the effect relationships of the sociocultural–psychological predictors on parents' intention to vaccinate their daughters. Results The study findings showed that parental decision-making regarding HPV vaccination was influenced by sociocultural and psychological factors. At the level of individual psychological factors, exposure to positive stories was significantly associated with perceived vaccine effectiveness (β = 0.331, t = 8.448, p < 0.001), which strongly predicted the attitude toward vaccination (β = 0.521, t = 8.133, p < 0.001); anticipated pride had more positive influence on vaccination-related decision-making (β = 0.156, t = 2.176, p < 0.05) than anticipated regret. In terms of social influence, injunctive norms on the Internet had a significantly positive influence on vaccination intention (β = 0.127, t = 2.382, p < 0.05), similar to descriptive norms (β = 0.135, t = 3.358, p < 0.01). Perceived moral obligation at the cultural level was the strongest predictor of parental decision-making regarding HPV vaccination (β = 0.193, t = 2.139, p < 0.05). Discussion This study is the first in mainland China to systematically examine the sociocultural-psychological predictors of parents' decision-making to vaccinate their 13–15-year-old daughters against HPV. A new extended TPB model with a sociocultural-psychological approach was developed. This model can support the investigation of factors affecting HPV vaccine uptake rates in the mainland Chinese population and similar populations and help to understand the differences in vaccination-related decision-making between Eastern and Western cultures. Furthermore, the study provided some suggestions for HPV vaccination communication campaigns targeting adolescent girls' parents.